Recent Advances in TiO2‐based Photoanodes for Photoelectrochemical Water Splitting. Issue 20 (8th September 2022) - Zhang, Xiaoyan; Zhang, Shengqi; Cui, Xiaoli; Zhou, Wei; Cao, Weimin; Cheng, Danhong; Sun, Yi
Abstract: Photoelectrochemical (PEC) water splitting has attracted great attention in the past several decades as it holds great promise to address global energy and environmental issues by converting solar energy into hydrogen. However, its low solar‐to‐hydrogen (STH) conversion efficiency remains a bottleneck for practical application. Developing efficient photoelectrocatalysts with high stability and high STH conversion efficiency is one of the key challenges. As a typical n‐type semiconductor, titanium dioxide (TiO2 ) exhibits high PEC water splitting performance, especially high chemical and photo stability. But, TiO2 has also disadvantages such as wide band gap and fast electron‐hole recombination rate, which seriously hinder its PEC performance. This review focuses on recent development in TiO2 ‐based photoanodes as well as some key fundamentals. The corresponding mechanisms and key factors for high STH, and controllable synthesis and modification strategies are highlighted in this review. We conclude finally with an outlook providing a critical perspective on future trends on TiO2 ‐based photoanodes for PEC water splitting. Abstract : This review summarizes the key parameters for developing advanced TiO2 photoanodes for photoelectrochemical (PEC) water splitting, mainly focusing on the synthesis of different nanostructured TiO2 thin film and the modification strategies such as morphology tuning, doping, and interface engineering. A critical perspective on future trends on TiO2 ‐based photoanodes for PEC water splitting is detailed to provide insight into the development of PEC with high solar‐to‐hydrogen conversion efficiency and stability.